Monitoring structural change in dynamic econometric models - Achim Zeileis; Friedrich Leisch; Christian Kleiber; Kurt Hornik (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2002)
The classical approach to testing for structural change employs retrospective tests using a historical data set of a given length. Here we consider a wide array of fluctuation-type tests in a monitoring situation – given a history period for which a regression relationship is known to be stable, we test whether incoming data are consistent with the previously established relationship. Procedures based on estimates of the regression coefficients are extended in three directions: we introduce (a) procedures based on OLS residuals, (b) rescaled statistics and (c) alternative asymptotic boundaries. Compared to the existing tests our extensions offer better power against certain alternatives, improved size in finite samples for dynamic models and ease of computation respectively. We apply our methods to two data sets, German M1 money demand and U.S. labor productivity.
Keywords: C22; C52; 519; Online monitoring; CUSUM; MOSUM; moving estimates; recursive estimates; Zeitreihenanalyse; Strukturbruch; Statistischer Test; Kontrolle; Theorie; Deutschland; USA; Ökonometrisches Modell